Driving simulation sickness and the sense of presence: Correlation and contributing factors. (April 2021) - Almallah, Mustafa; Hussain, Qinaat; Reinolsmann, Nora; Alhajyaseen, Wael K.M.
Highlights: Simulation sickness and the sense of presence are negatively correlated. Buildings replicated from real-world in scenarios could improve sense of presence. Well isolated simulation room could improve driver's involvement in experiments. Traveling speed is positively correlated with the simulation sickness severity. Females are more susceptible to simulation sickness symptoms. Abstract: Driving simulators are useful and effective tools for conducting studies in the field of traffic safety. Simulation sickness (SS) and the sense of presence (SP) are two well-known factors that could affect the results of the driving simulator experiments. This study investigated the relationship between SP and SS in a medium-fidelity driving simulator. Additionally, the impact of the road environment (urban arterials or rural expressways) on these subscales was investigated. Data was collected by means of self-reported questionnaires, which were conducted after the participants have driven the simulation scenarios in a fixed-base medium-fidelity driving simulator. A total of 125 drivers participated in this study. Results showed that females reported significantly higher SS scores than males. An increasing trend in the SS was observed with the increase of age. Importantly, designing buildings that replicate a real-world environment could increase SP and decrease SS. Moreover, designing high quality and resolution scenarios could also increase SP, thus decreasing the severity of SS symptoms. The results of this study can help researchers using medium-fidelity driving simulators to know the influencing factors for each subscale of SP on SS. Adjustments in the driving simulator and scenario settings as well as additional training exercises for higher speed scenarios can be beneficial in reducing the severity of SS.